ARTICULAR DEPRESSION: A NEW TYPE OF ANTE-MORTEM BONE ALTERATION IN THE FOSSIL RECORD OF TETRAPODA - Souza Barbosa, Fernando Henrique (Biosphere Comunicações Científicas, 2022)
Articular depression is a type of bone modification often found in extant animals recovered from archeological sites, but not yet formally described in fossil remains. Here, these depressions are formally described for the first time in extinct animals. The depressions were identified through macroscopically analyses performed in eight bones assigned to at least three Quaternary mammals (Eremotherium laurillardi, Ocnotherium giganteum and Toxodon sp.). It was possible to recognize Type 1, Type 3 and Type 4 depressions; Type 2 and Type 5 depressions were not identified in this sample. The etiology of articular depression is still unclear, but it seems to be related to osteochondrosis.